SAT Direct and Inverse Variation

Algebra Level 1

a a varies directly with b b .
b b varies indirectly with c c .

If the above statements are true for nonzero a , b , a, b, and c c , which of the following statements must be true?

(A) a \ \ a varies directly with c c and c c varies directly with a a .
(B) a \ \ a varies directly with c c and c c varies indirectly with a a .
(C) a \ \ a varies indirectly with c c and c c varies directly with a a .
(D) a \ \ a varies indirectly with c c and c c varies indirectly with a a .
(E) \ \ None of the above.

A B C D E

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tatiana Georgieva Staff
Feb 3, 2015

Correct Answer: D

Solution:

By the definition of direct variation, there is some constant k 1 k_1 such that a = k 1 b a = k_1 \cdot b .
By the definition of indirect variation, there is some constant k 2 k_2 such that b = k 2 1 c b = k_2 \cdot \frac{1}{c} .

As such, this gives

a = k 1 b = k 1 k 2 1 c . a = k_1 \cdot b = k_1 \cdot k_2 \cdot \frac{1}{c}.

This tells us that a a varies indirectly with c c .

Since we also have c = k 1 k 2 1 a c = k_1 \cdot k_2 \cdot \frac{1}{a} , thus c c varies indirectly with a a .

Hence the answer is (D).



Incorrect Choices:

(A)
If you set a a varying directly with b b and b b varying directly with c , c, you will get this wrong answer.

Also, if you set a a varying inversely with b b and b b varying inversely with c c , you will get this wrong answer

(B) and (C)
By definition, if y y varies directly with x x , then there is a nonzero constant k k for which y = k x . y=k\cdot x. Rearranging this we get x = 1 k y x= \frac{1}{k} y and hence x x varies directly with y . y.

Similarly, by definition, if y y varies inversely with x x , then there is a nonzero constant k k , such that y = k 1 x . y=k\cdot\frac{1}{x}. Rearranging this we obtain x = k 1 y , x=k\cdot \frac{1}{y}, and hence x x varies indirectly with y . y.

It is implied then that if a a varies directly with c , c, c c must vary directly with a , a, and if a a varies indirectly with c , c, c c must vary indirectly with a . a.

We conclude that these choices are wrong.

(E)
Answer choice (D) is correct.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...